1994
DOI: 10.1016/0005-2736(94)90177-5
|View full text |Cite
|
Sign up to set email alerts
|

Differential interaction of glimepiride and glibenclamide with the β-cell sulfonylurea receptor I. Binding characteristics

Abstract: Glimepiride is a novel sulfonylurea drug for treatment of non-insulin-dependent diabetes mellitus with higher blood sugar lowering efficacy in diabetic patients than glibenclamide raising the question whether this characteristics is in line with different binding of glimepiride and glibenclamide to the 0-cell sulfonylurea receptor. Scatchard plot analysis of [3H]sulfonylurea binding to membranes isolated from rat 0-cell tumors and (RINm5F) insulinoma cells and to RINm5F cells demonstrated that glimepiride has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0
10

Year Published

1994
1994
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(46 citation statements)
references
References 36 publications
1
35
0
10
Order By: Relevance
“…Molecular mass marker proteins for electrophoresis were obtained from Sigma, Deisenhofen, Germany. All other reagents and materials were purchased as described in the accompanying report [11]. Rats of the strain NEDH (New and protein was precipitated as published [12].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular mass marker proteins for electrophoresis were obtained from Sigma, Deisenhofen, Germany. All other reagents and materials were purchased as described in the accompanying report [11]. Rats of the strain NEDH (New and protein was precipitated as published [12].…”
Section: Methodsmentioning
confidence: 99%
“…
AbstractGlimepiride is a novel sulfonylurea for the treatment of type II-diabetic patients exhibiting different receptor binding kinetics to B-cell membranes with 8-9-fold higher kof f rate and 2.5-3-fold higher kon rate compared to glibenclamide (see accompanying paper (Miiller, G. et al (1994) Biochim. Biophys.
…”
mentioning
confidence: 99%
“…All the other materials and chemicals were obtained as described previously [11, 121. Cell culture and incubation of 3 T3 adipocytes. This was done according to published methods [11] with modifications: cells were grown (150 or 35 mm culture plates per condition) in DMEM (25 or 2 mL per condition) containing 25 mM glucose, 10% FCS and antibiotics. Confluent and differentiated cells (80-90% of the cells expressed the adipocyte phenotype) were washed twice with Krebs-Ringerphosphate buffer and then incubated in the same buffer (10 or 1 mL) with sulphonylurea or insulin as indicated.…”
Section: Materials Radiochemicals Were Bought Frommentioning
confidence: 99%
“…The mechanism behind the weight loss associated with glimepiride has not been established. However, it is likely that the lower insulin secretion stimulated by glimepiride relative to other SUs is involved [6,7,19,20]. Acute post-challenge hyperinsulinaemia predicts weight gain [21], and an intervention study in normoglycaemic, morbidly obese adolescents showed that metformin treatment led to greater weight loss than placebo [22].…”
Section: Discussionmentioning
confidence: 99%
“…Acute post-challenge hyperinsulinaemia predicts weight gain [21], and an intervention study in normoglycaemic, morbidly obese adolescents showed that metformin treatment led to greater weight loss than placebo [22]. Moreover, glimepiride also exerts a number of extrapancreatic, insulin-independent, glucose-lowering effects [6,7,20], and improved peripheral glucose uptake and decreased endogenous glucose production have both been observed after treatment with glimepiride [10]. These insulin-sparing effects of glimepiride could, therefore, explain the weight neutrality or weight loss associated with its use.…”
Section: Discussionmentioning
confidence: 99%